PEKERJAAN REHABILITASI JARINGAN IRIGASI DAERAH IRIGASI (D.I) TALUDUYUNU - Muhammad Januar Fuad; Nona Fitriana Madjowa; Aditya Maksum (Jurnal Pengabdian kepada Masyarakat (J-PMas), 2024)
The Taluduyunu Irrigation Area is one of the irrigation areas under Gorontalo Province, located in Pohuwato Regency. The current condition of the Taluduyunu irrigation area network is experiencing a lot of damage, especially to the secondary channels which causes leaks so that network function decreases and is not optimal. Therefore, rehabilitation and improvement of irrigation network facilities and infrastructure in the Taluduyunu irrigation area is needed. This service aims to help the contractor team as project implementers to carry out rehabilitation work in the Taluduyunu irrigation area network. The rehabilitation of the Taluduyunu regional network was carried out on a 12,140 meters long irrigation network with 566 hectares of affected agricultural land with the aim of increasing agricultural land production so that the local community's income would be better than before